Manual Sutureless Cataract Surgery (MSCS) in Patients with Pseudo-Exfoliation: Doi:10.36351/pjo.v36i4.1097 - Iqbal, Yasir; Khan, Qaim Ali; Zia, Sohail; Arshad Qureshi, Muhammad Usman; Hassan, Masud-ul- (Pakistan Journal of Ophthalmology, 2020)
Purpose: To document the complications of Manual suture-less cataract surgery in eyes with pseudo-exfoliation. Study Design: Interventional case series. Place and Duration of Study: Naseer memorial hospital, Dadyal, Azad Jammu Kashmir, from 4 July 2017 to 3 July 2019. Methods: One hundred and fifty patients with pseudo-exfoliation (PEX) and cataract were selected by convenient sampling. Patients with systemic diseases, history of trauma, intraocular pressure ?15 mm Hg on Applanation tonometry and any other associated ocular disease for example retinal detachment or retinal disease, previous history of glaucoma or narrow/closed angle on Gonioscopy were excluded from the study. Dark brown cataracts were also excluded. Pseudo-exfoliation was diagnosed on slit lamp on the basis of presence of dandruff like material on the pupil and the anterior lens capsule. The patients underwent manual suture less cataract surgery under local anesthesia Intraoperative and post-operative complications were noted. first day postoperatively. The collected data and analyzed using statistical package for social sciences (SPSS) version 21 for analysis. Results: The study group consisted of 64% males and 36% females with mean age of 65 ± 15.32 years. The most common difficulty encountered was poor pupil dilatation in 37.3% cases followed by Zonular dehiscence in 7.3%. On the first post-operative day, the most common complication was intraocular lens decentration in 2.6% of the cases. Conclusion: Pupils of patients with pseudo-exfoliation dilate poorly and makes surgery difficult. With good pupillary dilatation, careful capsulorhexis and minimal stress on the zonules, MSCS can be safely performed in eyes with cataract and PEX. Key Words: Pseudo-exfoliation, Cataract, Pupil.